The Future of MSMEs in Indonesia: Policy Directions for National Legal Formation in Supporting MSMEs Growth - Hidayat, Agi Attaubah; Ikhsan, Fachrial; Hafid, Numan Sofari; Rosidin, Utang; Permana, Ardian Agus (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This research explores the national legal formation policies that support the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, emphasizing their role as critical drivers of economic growth. Using a normative juridical method, the study evaluates recent regulatory reforms, such as the introduction of the Business Identification Number (NIB) and incentives for MSME partnerships. These initiatives simplify business formalization and enhance MSME competitiveness. The study applies Inclusive Growth Theory and Economic Analysis of Law (EAL) to propose policy directions that ensure equitable access to resources, digital transformation, and efficient regulatory environments. Recommendations highlight the need for adaptive and collaborative legal frameworks to strengthen MSMEs as pillars of inclusive and sustainable economic growth.